Doslidzhennya the electrical discharge in protective gases by oscillography. - Абрамов, О.О.; Завгородній, В.В. (Problems of Tribology, 2016)
The methods of obtaining ostsillohram, the determination of the relative breakdown gap and spark discharge parameters among different gases laboratory method. The influence of gas environment on the stability of the electric discharge, given comparative characteristics of each media. Ante relative breakdown discharge gap and parameters: voltage and current. The values of the relative gap breakdown, breakdown voltage and current electrical discharges in interelectrode gaps. Gases selected from the conditions of their greatest use in welding production: air, carbon dioxide, argon and argon mixture with carbon dioxide.